Post-Partum Depression: A Literature Review - Alami, Fathimah Nur; Maharani, Nyoman Ayu Anindya; Balqis, Ananda Amirah; Az-Zahra, Falira Khoirunnisa; Zahira, Lu’lu Al-Fatina; Tresna, I Made Gyanendra Nanda; Amalia, Emmy (Jurnal Biologi Tropis, 2024)
Post-partum depression (PPD) is a depressive episode that lasts up to four weeks after childbirth. Depression in mothers can affect various aspects of life, such as work, family, spouse, and children. There is a high incidence of suicidal thoughts in mothers who experience PPD, contributing significantly to maternal mortality rate. Understanding more about DPP is the main focus of this paper. This article utilizes a literature review method that collects sources from PubMed, Google Scholar, and Science Direct. This literature review explores various aspects of PPD including epidemiology, pathophysiology, clinical manifestations, diagnosis and treatment. Various physiological changes in the mother's body before and after childbirth increases the mother's vulnerabilities to mood disorders. The mechanisms of PPD involve various pathways, both external and internal. Internal factors include a decrease in certain hormones and neurotransmitters, a history of mental health disorders, and genetic predispositions. External factors include anxiety, external pressures, and lack of social support. The diagnosis of PPD can be established using the DSM-V and ICD-10 criteria. Treatment for PPD can involve both non-pharmacological and pharmacological therapies. PPD is a serious mental condition that causes various negative effects for both the mother and her family. The dysregulation of neuro-hormonal pathways is the primary mechanism in the pathogenesis of PPD. Effective diagnosis and appropriate treatment approaches are crucial in the management of PPD.